Chronic liver disease mortality in the United States, 1990–1998 - Vong, Sirenda; Bell, Beth P. (Hepatology (Baltimore, Md.), 2004)
In 1998, chronic liver disease (CLD) was the tenth leading cause of death in the U.S. Alcohol and hepatitis C are thought to be important etiologies. However, traditional methods for calculating CLD mortality rates from death certificates may underestimate hepatitis C‐related CLD mortality. We studied patterns of CLD deaths reported from 1990 through 1998, using an expanded definition that included death certificates where CLD, viral hepatitis, or CLD‐related sequelae were reported as the underlying cause. We calculated overall age‐specific and age‐adjusted mortality rates, and according to demographic characteristics and recorded causes, and evaluated trends using linear regression modeling. CLD mortality declined 5% overall from 1990 through 1994 (12.1 to 11.6/100,000; P = 0.002), but remained unchanged from 1995 through 1998 (P = 0.366). Decreases were similar for all causes except hepatitis C, for which rates increased 220% from 1993 to 1998 (0.57 to 1.67/100,000). Rates declined in all racial‐ethnic groups except American Indians and Alaska Natives (AI/AN), among whom rates were unchanged. Of 30,933 CLD deaths in 1998, 39% were coded as alcohol related, 15% as hepatitis C, 4% as hepatitis B, and 44% had no recorded cause. Age‐adjusted rates were higher among males (47.6/100,000) than females (32.2/100,000) and among Hispanics (19.1/100,000) compared with non‐Hispanics (10.8/100,000). Rates among AI/AN (28.7/100,000) were more than twice those of African Americans and whites (12.9/100,000 and 11.5/100,000, respectively). In conclusion, 1998 CLD deaths and the proportion attributable to viral hepatitis increased by 23% and 19%, respectively, compared with traditional methods. Mortality declines of the early 1990s were not sustained after 1994. Large disparities in CLD mortality remain, particularly among American Indians and Alaska Natives. (HEPATOLOGY 2004;39:476–483.)